Latino/a Children's and Young Adult Writers on the Art of Storytelling : Interviews with Latino/a Children's & Young Adult Fiction Authors - Aldama, Frederick Luis, 1969- (Book collections on Project MUSE., 2018)
"This book is an original collection of more than thirty interviews led by Frederick Luis Aldama with Latino/a authors working in the genre."